Ganglionated plexi ablation in the right atrium for the treatment of cardioinhibitory syncope. (26th April 2023) - Rebecchi, Marco; De Ruvo, Ermenegildo; Borrelli, Alessio; Sette, Antonella; Sgueglia, Marianna; Grieco, Domenico; Canestrelli, Stefano; Politano, Alessandro; Panattoni, Germana; Licciardello, Claudio; Latorre, Maria; Panuccio, Marco; et al.
Abstract: Neurocardiogenic syncope, also called vasovagal syncope, represents one of the clinical manifestations of neurally mediated syncopal syndrome. Generally, the prognosis of the cardioinhibitory form of neurocardiogenic syncope is good, but quality of life is seriously compromised in patients who experience severe forms. Drug therapy has not achieved good clinical results and very heterogeneous data come from studies regarding permanent cardiac pacing. In this scenario, the ganglionated plexi ablation has been proposed as an effective and safe method in patients with cardioinhibitory neurocardiogenic syncope, especially in young patients in order to avoid or prolong, as much as possible, the timing of definitive cardiac pacing. Certainly, making this procedure less extensive and limiting the ablation in the right atrium (avoiding the potential complications of a left atrial approach) and at level of anatomical regions of the most important ganglionated plexy, considered 'gateway' of the sino-atrial and atrio-ventricular node function (through the recognition of specific endocardial potentials), could be very advantageous in this clinical scenario. Finally, randomized, multicentre, clinical trials on a large population are needed to better understand which is the best ablation treatment (right-only or bi-atrial) and provide evidence for syncope guidelines.